2022
DOI: 10.1109/tase.2020.3041427
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Tremor Filtering Without Phase Distortion for Robotic Microsurgery

Abstract: All existing physiological tremor filtering algorithms, developed for robotic microsurgery, use non-linear phase pre-filters to isolate the tremor signal. Such filters cause phase distortion to the filtered tremor signal and limit the filtering accuracy. We revisited this long-standing problem to enable filtering of the physiological tremor without any phase distortion. We developed a combined estimation-prediction paradigm that offers zero-phase type filtering. The estimation is achieved with the mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Our analysis revealed that L = 70 and p = 33 are the optimized parameters of RVFL, as illustrated in Figure 4b. These hyperparameters are employed to optimize the C and k with EMD-RVFL over the same 50 random traces to yield the least RMSE [58]. As depicted in Figure 4c, it is evident that EMD-RVFL achieved the lowest RMSE at C = 10 × 10 9 and k = 7.…”
Section: Optimization Of Hyperparametersmentioning
confidence: 99%
“…Our analysis revealed that L = 70 and p = 33 are the optimized parameters of RVFL, as illustrated in Figure 4b. These hyperparameters are employed to optimize the C and k with EMD-RVFL over the same 50 random traces to yield the least RMSE [58]. As depicted in Figure 4c, it is evident that EMD-RVFL achieved the lowest RMSE at C = 10 × 10 9 and k = 7.…”
Section: Optimization Of Hyperparametersmentioning
confidence: 99%
“…During this procedure, the control variable u may violate the constraint conditions given that the bounded noises are manipulated by the filter. On the other hand, the nature of this process makes it vulnerable to phase distortion [15]. In addition to violating the given constraints, the control sequence will diverge if the noises are overlapped repeatedly and amplified over time.…”
Section: A Limitations Of External Smoothing Algorithmsmentioning
confidence: 99%